Comparison of the Effectiveness of Intraarticular Ozone Therapy and Platelet Rich Plasma Treatment in Patients with Knee Osteoarthritis - Yalçın, Ümit (International Journal of Innovative Research in Medical Science, 2020)
Background: Platelet rich plasma (PRP) has been applied for a long time in osteoarthritis (OA). Although there are studies about PRP that examining the effectiveness with agents such as hyaluronic acid and corticosteroid, there are few published literature comparing with ozone therapy (OT). The aim of this study is to compare the pain severity and functional status of OA patients undergoing intraarticular ozone and PRP injections. Methods: In a study which is made as prospective, randomized controlled study (RCS), 49 patients were included the study. In the first group (n = 24) OT, in the second group (n = 25) PRP injections were administered intraarticularly 3 times in total with one week intervals. Visual pain scale (VAS) and severity of pain were compared with Western Ontario McMaster Osteoarthritis Index (WOMAC). Results: In the PRP group, WOMAC pain, physical function and WOMAC total score were significantly lower than the OT group (p ˂ 0.05). Although VAS score decreased significantly (p ˂ 0.05) after treatment in both groups compared to pretreatment, the VAS score in the PRP group was significantly (p ˂ 0.05) lower than the OT group after treatment. Conclusion: Our study contributes to the literature in terms of limited publication about OT. However, this study shows that the results of PRP treatment are superior to OT in the treatment of knee OA.